Knowledge and Perceptions on Antenatal Care among Men in Embakasi South Sub County, Nairobi, Kenya - Kinoti, Fred Kirimi; Fava, Salvatore (Journal of Maternal and Child Health, 2022)
Background: Involving husbands and men in decision-making processes can play a crucial role in antenatal care uptake and utilisation. However, men often lack necessary knowledge and have misleading beliefs and perceptions. Subjects and Method: The current research was an analytical cross sectional study conducted in Embakasi South Sub county, Nairobi, Kenya which sought to assess the knowledge and attitude towards antenatal care among men. Kelsey et al sample size determination formula was used to calculate a sample of 66 subjects. A researcher-administered questionnaire was used to collect data. Descriptive statistics and chi-square analyses were used in the analysis of data with the help of SPSS. Results: The results in this study showed that slightly above half (57.6%, n=38) of the subjects had low knowledge. Slightly above half (51.5%, n=34) had positive attitudes towards ANC. None of the demographic characteristics was significant to knowledge. There was also no significant associations between demographic characteristics and subjects’ attitudes towards antenatal care. There was a significant association (p =0.048) between knowledge and attitudes. Results showed that subjects with low knowledge were 2.196 times likely to have positive attitudes. Conclusion: These findings highlight the current knowledge gap that exists among men regarding antenatal care. An education intervention program ought to be carried out among men in Embakasi South Sub County and other parts of Nairobi and the country. Community health programs should also build on the positive attitudes towards ANC as found in this study to help improve male involvement in antenatal care and other reproductive health issues.